Dispatchable solar power using molten salt directly irradiated from above. (15th May 2021) - Calvet, Nicolas; Slocum, Alexander H.; Gil, Antoni; Grange, Benjamin; Lahlou, Radia; Hamer, Tyler T.; Diago, Miguel; Tetreault-Friend, Melanie; Codd, Daniel S.; Trumper, David L.; Armstrong, Peter R.
Highlights: A new concentrating solar power receiver with integral thermal storage has been demonstrated in field conditions. System behavior has been captured with varying operating schemes and for extended durations. For the first time in situ initial melting, and subsequent freeze recovery, of solar salt heat transfer fluid has been demonstrated. It is the world's first direct absorption molten salt receiver pilot successfully tested in real conditions with a solar facility. Abstract: Concentrating solar power (CSP) with thermal energy storage (TES) presents the major advantage over solar photovoltaics of dispatchability . High thermodynamic efficiencies achieved by collecting and storing heat at higher temperatures, and recent maturing of the technology, are making molten-salt central receiver plants the preferred option for CSP. To explore potential further improvements in CSP efficiency and cost the world's first direct absorption molten salt volumetric receiver/storage system was built at pilot scale, commissioned and monitored. In this demonstration a 100 kWth beam-down tower directs solar radiation through a final concentrator into the open aperture of a 1.94 m high and 1.25 m internal diameter tank receiver situated near the ground. The receiver tank is filled with 3, 800 kg of 60–40 wt% NaNO3 -KNO3 and serves as a stratified or mixed single tank thermal store that can satisfy evening peak loads or provide baseload power through the night. Compared to the parasitic loads of a conventional tower-receiver plant, the energy needed for salt transport from receiver to TES and morning preheat is negligible for this new system. The hot-spot problem of tubular receivers is eliminated and. the combined receiver/storage tank reduces component costs. In-situ initial melting was accomplished using solar energy as the primary input. Thermal stratification was maintained by daily cycling of a divider plate and occasional mixing plate actions and hot spots were never observed during several months' operation between 250 and 500 °C. Three cycles of complete salt freezing and in-situ on-sun re-melting were tested with no operational difficulty and no discernible damage.